Value addition through digitalization for Ugandan coffee farmers - Muwonge, David (Technical Centre for Agricultural and Rural Cooperation, 2018)
A digital farmer profiling initiative, which enables coffee to be traced back to its roots, is paying off for smallholder farmers in Uganda. NUCAFE's David Muwonge describes how coffee produced under the scheme is fetching far higher prices, revealing the strong potential of geo-referencing as a marketing tool to guarantee authenticity and origin.